One-pot synthesis of folic acid encapsulated upconversion nanoscale metal organic frameworks for targeting, imaging and pH responsive drug release. Issue 45 (27th October 2016) - Chowdhuri, Angshuman Ray; Laha, Dipranjan; Pal, Srimanta; Karmakar, Parimal; Sahu, Sumanta Kumar
Abstract : A folic acid conjugated upconversion nanoscale metal organic framework is developed as a smart material in one step for targeted anticancer drug delivery. Abstract : In this work, a new theranostic nanoplatform is developed to construct an anticancer drug carrier by integrating the distinct advantages of upconversion nanoparticles (UCNPs) and metal organic frameworks (MOFs) encapsulated with a targeting ligand. Here NaYF4 :Yb 3+, Er 3+ is chosen as an upconversion nanoparticle for its high luminescence properties. Then, folic acid encapsulated Zeolitic Imidazolate Framework-8 (ZIF-8) is directly coated on UCNPs in one step to form a monodispersed core–shell structured nanocomposite (labeled as UCNPs@ZIF-8/FA). The synthesized upconversion nanoscale MOFs (NMOFs) are simultaneously used as a targeted anticancer drug carrier and in cellular imaging. The UCNP@ZIF-8/FA nanocomposites are found to be nontoxic towards the human cervix adenocarcinoma (HeLa) and mouse fibroblast (L929) cell lines via a cell viability assay. It is worthwhile noting that, the anticancer drug 5-fluorouracil (5-FU) is absorbed into UCNP@ZIF-8/FA nanocomposites (loading amount 685 mg g −1 ) and also pH responsive drug release is observed. The as-prepared 5-FU loaded UCNP@ZIF-8/FA nanocomposites exhibited greater cytotoxicity towards HeLa cells due to the folate receptor-mediated endocytosis. Our study highlights the potential of developing multifunctional upconversion NMOFs for simultaneous targeted cellular imaging with delivery of anticancer drugs.